2017
DOI: 10.4269/ajtmh.16-1008
|View full text |Cite
|
Sign up to set email alerts
|

Low Prevalence of Substandard and Falsified Antimalarial and Antibiotic Medicines in Public and Faith-Based Health Facilities of Southern Malawi

Abstract: Substandard and falsified antimalarial and antibiotic medicines represent a serious problem for public health, especially in low- and middle-income countries. However, information on the prevalence of poor-quality medicines is limited. In the present study, samples of six antimalarial and six antibiotic medicines were collected from 31 health facilities and drug outlets in southern Malawi. Random sampling was used in the selection of health facilities. For sample collection, an overt approach was used in licen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 25 publications
(59 reference statements)
5
59
2
Order By: Relevance
“…Prices of medicine samples which were found not comply with pharmacopeial specifications [22] are underlined . 1 Not included in calculations, see Methods. 2 Prices of artemether/lumefantrine were not included in the calculation of the overall median price ratio for CHAM and private facilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prices of medicine samples which were found not comply with pharmacopeial specifications [22] are underlined . 1 Not included in calculations, see Methods. 2 Prices of artemether/lumefantrine were not included in the calculation of the overall median price ratio for CHAM and private facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Prices of medicine samples which were found not comply with pharmacopeial specifications [22] are underlined .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that ±10%variations in TLC readings can be seen with the naked eye, medicines with 70–80% of the API that otherwise meet quality standards could be acceptable. 21,23,24 However, as TLC may mistakenly identify a form as having too little or sufficient API, reader experience is important for accurate interpretation. 24 Conversely, the detection of breakdown products of the API by TLC due to, for example, incorrect storage, can lend confidence to an interpretation of too little drug.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Tanzania has reported a failure rate of only 4.8% for antimalarial drugs collected between 2012 and 2015 . A likewise low prevalence of substandard and falsified antimalarial medicines (and also in the case of antibiotic pharmaceutical preparations) has recently been found in Southern Malawi …”
Section: Introductionmentioning
confidence: 99%